Pengaruh Produksi, Ekspor Dan Investasi Industri Otomotif Terhadap PDB Sektor Manufaktur Di Indonesia - Sonya Khasrisma Budiono; Budi Prayitno; Eva Wany (widya balina, 2025)
The purpose of this study is to analyze the influence of production, exports and investment on the GDP of the Manufacturing Sector in Indonesia. This study uses a descriptive quantitative approach with time series data 2017-2024, the data used is secondary data taken by GAIKINDO (Association of Indonesian Automotive Industries) and the National Statistics Agency with multiple linear regression analysis techniques interpreted using Eviews 13. The results of the T-test study on the production, export and investment variables have no significant effect. However, the results of the F-test of the production, export and investment variables have a simultaneous effect on the GDP of the Indonesian Manufacturing Sector. From the results of the determinant test (R2) the independent variable is 85%, while the remaining 15% is influenced by other variables from this study.